Cloud computing concept, classifications, applications and challenges - Abd S.K.; Al-Haddad S.; Hashim F.; Abdullah A.B.; Yussof S. (Serials Publications, 2023)
Recently, cloud computing has appeared as a modern technology used to host and deliver services over the Internet. Business owners see the cloud as an interesting technology because it abrogates the demand for customers to plan ahead for provisioning. In addition, the cloud simplifies infrastructure planning for new companies starting as small businesses and enables extra resources to be added only if there are many requests for services. Cloud computing can be represented as a technological revolution in the world of the IT industry; however, cloud evolution is presently in its infancy, accompanied by many challenges that should be addressed. In this paper, an inclusive study of cloud computing is presented, highlighting its main concept including its definition and classifications, architecture, famous applications, serious challenges and popularly used simulators. The goal of this study is to offer better comprehension of the cloud computing design issues and to identify significant research trends in this increasingly significant area.